Eradicating a Culture of Public Mistrust in TVET College Education in South Africa: A Manifesto for the Sector’s Sustainability Ahead of 4IR - Nkambule, Bongani Innocent; Ngubane, Sindile Amina (Research in Social Sciences and Technology, 2023)
The consumption of technical and vocational education and training has increased exponentially over the past two decades. In terms of inclusion, it is without a doubt that today’s TVET sector is a far cry from what it was before the democratic government took over the baton from the apartheid government. TVET has become a refuge to many hopefuls from the historically disadvantaged sectors of society who, due to a range of apparent reasons, would ordinarily not have managed to partake in tertiary education. To many South African youth, TVET presents an avenue for the acquisition of a skill that will give them a fighting chance at escaping the harsh recurrence of poverty, economic inactivity and resource deprivation they are subjected to almost on a daily basis. However, beneath this silver lining lies a growing public disgruntlement over the TVET system’s ability to steadfastly deliver quality education and transform the lives of students, by instilling in them agency for self-regulated and collaborative innovation that will turn them into formidable and assertive role players in the knowledge societies, come the fourth industrial revolution (4IR). To understand the crux of public mistrust in TVET college education in South Africa, an extensive body of literature was reviewed. The findings of the paper point to strategic factors (which in the main are attributed to a lack of effective leadership and managerial skills) and contextual factors that occur at a campus level, as major causes of public mistrust in TVET education. The paper concludes by tabling a manifesto for changing the status quo ahead of the advent of 4IR.